Preparation of Water‐in‐Oil Microemulsion from the Mixtures of Castor Oil and Sunflower Oil as Makeup Remover. Issue 6 (13th August 2018) - Pakkang, Nutthira; Uraki, Yasumitsu; Koda, Keiichi; Nithitanakul, Manit; Charoensaeng, Ampira
Abstract: Cosmetics accumulated in facial skin are difficult to remove by ordinary cleansers because they normally contain highly waterproof ingredients. Therefore, development of makeup remover products is necessary for the efficient removal of cosmetics without irritation to the skin. Current commercial makeup removers are emulsions produced from mineral oil and water with surfactants sometimes cause allergies and acne. To overcome these problems, vegetable oils seem to be promising ingredients for makeup removers. In this study, such makeup removers were prepared as water‐in‐oil (w/o) microemulsion from a mixture of castor oil and sunflower oil at ratios from 1:9 to 5:5 and water with nonionic surfactants, Span ® 80 and Dehydol LS ® TH. The remover candidates were selected with respect to transparency of emulsion and cleansing efficiency. As a result, an emulsion was prepared from a mixture of castor oil and sunflower oil with the ratio of 3:7, Dehydol LS ® TH with 7 repeating units of ethylene oxide, and 7.0% (w/w) of water. It was found that the stability of transparency and a high cleansing efficiency were attributed to the hydrophilicity of the surfactant and castor oil. Dynamic light‐scattering analysis demonstrated that the emulsion consisted of nanoscale micelles, resulting in a microemulsion.